A Comparison of Suicide Attempt Histories of Pediatric and Adult Medical Inpatients and Implications for Screening. Issue 3 (3rd July 2022) - Mournet, Annabelle M.; Bridge, Jeffrey A.; Ross, Abigail; Powell, Daniel; Snyder, Deborah J.; Claassen, Cynthia A.; Wharff, Elizabeth A.; Pao, Maryland; Horowitz, Lisa M.
Abstract: Objective: A suicide attempt is the most potent predictor of future suicidal behavior, yet little is known about how to manage and respond to reports of attempt histories in hospitalized medical patients. This study aims to describe the prevalence and characteristics of pediatric and adult medical inpatients who report a past suicide attempt. Method: Participants were medical inpatients, aged 10–93 years, enrolled in two suicide risk screening instrument validation studies. Participants completed the Ask Suicide-Screening Questions (ASQ) and the Patient Health Questionnaire (PHQ). Results: A total of 1324 medical inpatients (624 pediatric, 700 adult) completed the ASQ, with 114 participants (8.6%) reporting a past suicide attempt (51 pediatric; 63 adults). Comparing youth to adults, there was no significant difference between attempt rates ( χ 2 =0.29, p  = 0.59). Youth with a past attempt were significantly more likely to report past week suicidal ideation (OR = 28.22; 95% CI = 5.90, 135.06) and have a history of mental health care (OR = 9.11; 95% CI = 2.59–32.10), compared to those without a past attempt. Adults with a past attempt were significantly more likely to screen positive for depression, compared to those without attempt histories (OR = 5.00; 95% CI = 2.31–10.83). Conclusions: Nearly 9% of hospitalized medical patients endorsed a past suicide attempt when screened. Since adolescence is a critical time for detecting suicide risk, screening that includes past suicidal behavior may be an important means to identify youth with recent suicidal thoughts. By assessing recency of suicide attempts in adults, medical settings may optimize the effectiveness of how positive suicide risk screens are managed. HIGHLIGHTS: Roughly 9% of medical patients reported a past suicide attempt when screened. Adolescence is a critical time for detecting suicide risk and intervening. Assessing past suicide attempts in adults can help with managing positive screens.